Isotopic Analysis of NUSIMEP-6 Uranium Particles using SEM-TIMS - Jong-Ho Park (Mass Spectrometry Letters, 2013)
Isotopic analysis using thermal ionization mass spectrometry coupled with scanning electron microscopy (SEMTIMS) was performed to determine the isotopic ratios of uranium contained in micro-particles in the 6th Nuclear Signatures Interlaboratory Measurement Evaluation Programme (NUSIMEP-6) sample. Elemental analysis by energy dispersive X-ray spectroscopy (EDS) was conducted on uranium-bearing mirco-particles, which were transferred to rhenium filaments for TIMS loading using a micromanipulation system in a SEM. A multi-ion-counter system was utilized to detect the ion signals of the four isotopes of uranium simultaneously. The isotope ratios of uranium corrected by bracketing using a reference material showed excellent agreement with the certified values. The measurement accuracy for n(234U)/n(238U) and (b) n(235U)/n(238U) was 10% and 1%, respectively, which met the requirements for qualification for the NetWork of Analytical Laboratories (NWAL).